FATORES ASSOCIADOS À SAÚDE BUCAL E QUALIDADE DE VIDA EM ADOLESCENTES DE 12 ANOS - JHENYFFER ANDRADE VIANA (2024)
This study analyzed factors associated with the quality of life and oral health of 12-year-old adolescents. Data were collected from 615 adolescents in the five largest cities of Mato Grosso do Sul, Brazil. The theoretical framework of social determinants of oral health guided all analyses, and the instrument used to measure oral health-related quality of life was the Oral Impacts on Daily Performances (OIDP) questionnaire. Variables analyzed included oral health-related quality of life, unhealthy eating habits, sedentary behavior, experience of dental caries, access to fluoridated water, sociodemographic characteristics, and health behaviors. Considering sample weights, 43% of adolescents reported some impact on their oral health-related quality of life (OIDP≥1). In adjusted models, higher consumption of unhealthy foods (moderate and high) was associated with both prevalence [OR=3.59 (95% CI 1.99; 6.46)] and severity [RR=2.05 (95% CI 1.43; 2.94)] of impacts on oral health-related quality of life compared to their counterparts. The prevalence of tooth loss was 5% (95% CI 1.9; 8.0%). In adjusted models, family income below the poverty line [OR=2.81 (95% CI 0.93; 8.52)], high consumption of unhealthy foods [OR=1.93 (95% CI 0.54; 6.87)], and sedentary behavior (≥ 2 hours/day) [OR=1.77 (95% CI 1.28; 2.45)] were associated with tooth loss. Access to fluoridated water was a protective factor [OR=0.40 (95% CI 0.16; 0.99)]. The implementation of intersectoral public policies aimed at promoting healthy eating and reducing sedentary behavior can have a significant positive impact on the quality of life of adolescents. Additionally, access to fluoridated water is an important protective factor against tooth loss in this age group. The Family Health Strategy (ESF), as the coordinator of care, plays an important role by promoting comprehensive and continuous monitoring of families, strengthening the effects of these public policies, and ensuring healthy and sustainable development for adolescents. Descriptors: Family Health Strategy, Feeding Behavior, Sedentary behavior, Quality of life, Tooth loss.